Primary malignant peripheral nerve sheath tumor of the pleural cavity: rapid progression - Misiak, Piotr; Wcislo, Szymon; Jabłoński, Sławomir; Szwalbe, Katarzyna (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2014)
Malignant peripheral nerve sheath tumor (MPNST) accounts for 5-10% of all malignant soft tissue tumors. It often affects the extremities and abdominal cavity and very rarely develops in the thoracic cavity. The incidence in the general population is 0.001%. In our paper we would like to present a case report of a 74-year-old female patient with primary MPNST of the pleural cavity which was previously misdiagnosed as a non-small cell lung cancer. Despite the combined treatment, after four months the patient developed a secondary tumor in the contralateral pleural cavity which was also treated operatively.